PENGARUH GOOD CORPORATE GOVERNANCE (STRUKTUR KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL) TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BEI 2017 – 2019 - Zara Tania Rahmadi,; M. Aria Wahyudi, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study was conducted to determine the effect of good corporate governance on firm value. The good corporate governance variable is measured using institutional ownership and managerial ownership variables, while the firm value is proxied by Tobin's Q. The object of this research is manufacturing sector companies for 3 years from 2017-2019, totaling 122 companies with a sample of 12 companies. The analytical method used is panel data regression with SPSS 26 statistical test tool. The test results show that institutional ownership and managerial ownership have a significant effect on firm value. It can be concluded that the implementation of good corporate governance in a company can avoid agency conflicts within the company so that it can directly have a good influence on the value of the company and can provide added value for investors in choosing the company they want to invest in.